2021
DOI: 10.3390/electronics10131583
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hybrid Meander Structures with Additional Shields

Abstract: Models of hybrid meander structures with additional shields are presented in this paper. The influence of additional shields and their grounding positions on the electromagnetic characteristics of the hybrid meander structures was investigated. Three-dimensional models were created and analyzed using the method of moments (MoM) in the Sonnet® and finite-difference time-domain (FDTD) method in CST Microwave Studio® commercial software packages. The computer-based modeling was verified by physical experiment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our previous research [40] showed positive features of the meander structures when the passband, delay time, and input impedance characteristics could be controlled without changing the dimensions of the overall meander structure. In this article, the miniaturization task was solved when the overall size of the meander structure was reduced from 16.24 × 17.35 × 0.291 mm till 8.40 × 17.35 × 0.76 mm while maintaining the same electrodynamical parameters of the meander structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research [40] showed positive features of the meander structures when the passband, delay time, and input impedance characteristics could be controlled without changing the dimensions of the overall meander structure. In this article, the miniaturization task was solved when the overall size of the meander structure was reduced from 16.24 × 17.35 × 0.291 mm till 8.40 × 17.35 × 0.76 mm while maintaining the same electrodynamical parameters of the meander structure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the multilayer meander structure under study might be used in the filter technologies in the ISM frequency band, where miniaturization is one of the biggest issues [38,39]. The initial conventional single-layer meander structure is taken from our earlier research [40], whose dimensions are discussed in the materials and methods section. The influence of a routing meander conductor through several layers on the operational parameters of the meander structure is investigated in detail.…”
Section: Introductionmentioning
confidence: 99%